Decreasing Frontal Electroencephalogram Alpha Power and Increasing Sensitivity to Volatile Anesthetics Over 3 Surgeries Within 7 Months: A Case Report. Issue 7 (1st October 2019) - Kaiser, Heiko A.; Hirschi, Trevor; Hartwich, Volker; Stucki, Monika; Rummel, Christian; Reineke, David; Hight, Darren
Abstract : Depth of anesthesia (DoA) monitors are widely used during general anesthesia to guide individualized dosing of hypnotics. Other than age and specific drugs, there are few reports on which comorbidities may influence the brain and the resultant electroencephalogram (EEG) of patients undergoing general anesthesia. We present a case of a patient undergoing 3 cardiac operations within 7 months with severe illness and comorbidity, leading to pronounced physical frailty and significant changes of frontal alpha power in the EEG and increased sensitivity to volatile anesthetics. These findings may have important clinical implications and should trigger further investigations on this topic.